Perancangan E-Marketspace Teripang dengan Web Information System Development Methodology - Rismayani Rismayani; Febri Hidayat Saputra; Mashud Mashud (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The use of technology in website-based buying and selling transactions has grown rapidly, especially in e-commerce. However, marketing of processed sea cucumber products is still done conventionally, which causes limited market reach and transaction efficiency. This study aims to develop a web-based e-marketspace system to improve the effectiveness of marketing and transactions of processed sea cucumber products. The method used in this study is the Web Information System Development Methodology (WISDM), which allows for rapid and sustainable system development according to user needs. The results of the study indicate that the system developed can improve transaction efficiency, expand marketing reach, the development of a website-based e-marketspace system for selling sea cucumbers can provide significant benefits for business actors in increasing efficiency and marketing reach. This system simplifies the transaction process by providing a digital platform that can be accessed by customers widely, thus supporting the growth of the marine product industry, especially processed sea cucumber products.